2017
DOI: 10.3171/2016.9.jns161176
|View full text |Cite
|
Sign up to set email alerts
|

Early and late epilepsy surgery in focal epilepsies associated with long-term epilepsy-associated tumors

Abstract: OBJECTIVE Epilepsy surgery is an effective means of treating focal epilepsy associated with long-term epilepsy-associated tumors. This study evaluated a large population of surgically treated patients with childhood onset of epilepsy and a histologically confirmed diagnosis of long-term epilepsy-associated tumors. The authors analyzed long-term seizure outcomes to establish whether the time of surgery and patients' ages were determinant factors. METHODS The authors separately investigated several presurgical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
63
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 38 publications
10
63
1
3
Order By: Relevance
“…When pooling multiple lesion types, completeness of lesionectomy has been correlated with seizure freedom in one large cohort of SEEG-guided resections. 3 Indeed, completeness of lesionectomy has classically been associated with seizure freedom in the setting of epilepsy-associated tumors, 30 FCD, 31,32 cavernoma, 33 and posttraumatic encephalomalacia involving the frontal lobe. 34 However, completeness of lesionectomy has not been shown to correlate with seizure freedom in other lesion types such as polymicrogyria 3,15 and PNH.…”
Section: Discussionmentioning
confidence: 99%
“…When pooling multiple lesion types, completeness of lesionectomy has been correlated with seizure freedom in one large cohort of SEEG-guided resections. 3 Indeed, completeness of lesionectomy has classically been associated with seizure freedom in the setting of epilepsy-associated tumors, 30 FCD, 31,32 cavernoma, 33 and posttraumatic encephalomalacia involving the frontal lobe. 34 However, completeness of lesionectomy has not been shown to correlate with seizure freedom in other lesion types such as polymicrogyria 3,15 and PNH.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] For this group of tumors the acronym "LEATs" (longterm epilepsy associated tumors) was proposed by Luyken et al 1 By definition, "long term" means causing drug-resistant seizures for 2 years or more. [1][2][3][4][5][6][7][8][9][10][11][12][13] For this group of tumors the acronym "LEATs" (longterm epilepsy associated tumors) was proposed by Luyken et al 1 By definition, "long term" means causing drug-resistant seizures for 2 years or more.…”
mentioning
confidence: 99%
“…6,7,12,[14][15][16][17][18] Accordingly, it has been recently proposed to maintain the acronym LEATs, changing its meaning to "low grade epilepsy associated neuroepithelial tumors." 6,7,12,[14][15][16][17][18] Accordingly, it has been recently proposed to maintain the acronym LEATs, changing its meaning to "low grade epilepsy associated neuroepithelial tumors."…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Pelliccia et al reported that pediatric patients are more responsive to epilepsy surgery than adults. [9] Their analysis also found that temporal lobe localization, complete resection and shorter duration of epilepsy were the determinant factors for a favorable postoperative seizure outcome. Their findings also supported the early removal of LEATs to achieve better seizure freedom and improve cognitive development.…”
Section: The Clinical Management With Antiepileptic Medicationsmentioning
confidence: 99%